Ranking Algarve Tourists Preferences: An Ordered Probit Approach - Serra, Jaime (2014)
The starting point for tourism development is tourists’ preferences. Preferences are the cognitive motivations that drive tourists to a certain destination. There are a plethora of published studies in the field of tourist motivations, such as Dann (1977); Crompton (1979); Witt and Wright (1992); Pearce and Lee (2005) to name a few, who contributed to the understanding of this area of research. However, research which focus on motivations’ dynamics overtime is scant if not non-existent. This is even more critical as these preferences assume a dynamics that challenges the need to foresee tourist preferences over the years. This paper aims to rank Algarve tourists’ preferences, in a leisure continuum from 2007 up to 2010. Ordered probit models were employed in order to rank and classify preferences by year, taking into account market heterogeneity. Preference turning-points and continuity points are depicted to illustrate the dynamics of tourist preferences. Data were obtained from a survey applied to international tourists who spent their holidays in Algarve. The population of the study is matched to all international tourists visiting Algarve for the purpose of holidays/leisure. Questionnaires were administrated in the airport departures lounge. Over the four years in which the administration of this questionnaire occurred the interviews were made randomly to the most nearby person. A total of 15554 persons were interviewed from which, 2636 questionnaires were collected in 2007; 2187 in 2008; 5938 in 2009 and 4781 in 2010. Results revealed dynamic motivations in several markets. The Algarve reveals a potential to attract new and repeat visitors that goes beyond its main competitive advantage, the sun and sea. Managerial implications of the results are discussed.